Intuition as a capacity, personality level and style of functioning. Synthetic overview of some psychological views - Karwowski, Maciej (Studia Psychologica: Theoria et praxis, 2006)
The article assumes problems of psychology of intuition. There are discussed basic problems associated with psychological conceptions of intuition: intuition as a cognitive style, personality characteristics, and cognitive ability. On the basis of cited theories there is proposed binary understanding of intuition and people, who use intuition. First dimension concentrates on intuition as a preference and style . looking from this point of view people can be divided between intuitionists and rationalists. Second one point of view concentrates on efficiency of using intuition (intuitional intelligence) . looking from this point on view intuitionists can be divided between: intuitics (efficient intuitionists) and guessers (nonefficient intuitionists), and rationalists between: logics (efficient rationalists) and weak (nonefficient rationalists).